Identifikasi Rhodamin B Pada Sambal Botol Yang Diperjualbelikan Di Sekitar Jalan Abdul Kadir Kota Makassar - Riska Kadir; Andi Auliyah Warsyidah; Nahir Bandu (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2018)
The use of Rhodamin B in foods for long periods of time can lead to health problems. However, if exposed to large amounts of Rhodamin B, an acute symptom of poisoning will occur shortly. The purpose of this study was to find out whether Rhodamin B was in Sambal Botol which was traded around Jalan Abdul Kadir, Makassar City. The type of research used was descriptive, namely seeing a picture of Rhodamin B on a bottle of chili. The population in this study were all bottle sambals that were traded around the streets of Abdul Kadir Kota Makassar. The sample used was three samples of bottle chili with different brands. The sampling technique using purposive sampling is based on certain criteria. This research was conducted on 30 August 2017 in the eastern Indonesian university pharmacy laboratory. From the results of the analysis of three samples, there was no Rhodamine B coloring agent. The benefits of the study were to provide information to consumers to remain cautious in consuming bottled sambal traded around Abdul Kadir Street, Makassar City.